Diversitas Eksistensialisme: Analisis Kritis Perspektif Teologis-Filosofis - Yornan Masinambow; Nahor Banfatin; Debbie Y. Refialy (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
The purpose of this article is to describe and analyze the notion of diversity in existentialism that appears in existentialist thinkers namely Soren Kierkegaard, Jean Paul Sartre, and Paul Tillich who have their own characteristics in their thinking. The theme of Existentialism has been discussed throughout history because it focuses on human concerns. A qualitative method with a content analysis approach is used to discuss and analyze existentialism philosophically and theologically. Based on the analysis, existentialism refers to humans as conscious subjects but can be viewed differently by thinkers. Kierkegaard’s theistic existensialism with the concept of leap of faith where humans are fully conscious can relate personally with God. Sartre's existentialism is atheistic, rejecting the existence of God and emphasizing human subjects who determine their own lives, taking responsibility for themselves. Tillich who uses the theme of existentialism in his method of correlation to connect God's Word to modern people with their existential awareness. Existentialism is very anthropocentric and does not emphasize Theocentric in human live.